Value of big data to finance: observations on an internet credit Service Company in China - Shaofeng Zhang; Wei Xiong; Wancheng Ni; Xin Li (Financial Innovation, 2015)
Background: his paper presents a case study on 100Credit, an Internet credit service provider in China. 100Credit began as an IT company specializing in e-commerce recommendation before getting into the credit rating business. The company makes use of Big Data on multiple aspects of individuals' online activities to infer their potential credit risk. Methods: Based on 100Credit's business practices, this paper summarizes four aspects related to the value of Big Data in Internet credit services. Results: 1) value from large data volume that provides access to more borrowers; 2) value from prediction correctness in reducing lenders' operational cost; 3) value from the variety of services catering to different needs of lenders; and 4) value from information protection to sustain credit service businesses. Conclusion: The paper also discusses the opportunities and challenges of Big Data-based credit risk analysis, which needs to be improved in future research and practice.
Keywords: 650; Big data; Credit rating; Information economics; Value of information; Finance